Evaluation of Anti-Aging Activity of the Biofield Energy Treated Novel Test Formulation Using SIRT1 and Telomerase Activity in in Vitro Model - Mahendra, Kumar Trivedi; Snehasis, Jana (Journal of Aging Research And Healthcare, 2019)
Telomerase and SIRT1 (member of the sirtuin protein family) along with the lifestyle and diet are the major determinants of aging and its associated diseases such as cancer and cardiovascular disorders. The study objective was to investigate the effect of Consciousness Energy Healing based novel test formulation in pre-adipocytes (3T3-L1) and human peripheral blood mononuclear cells (PBMCs) for anti-aging activity using SIRT1 and telomerase assay. The test formulation was divided into two parts. One portion was denoted as the untreated test item without any Biofield Energy Treatment, while the other portion was defined as the Biofield Energy Healing Treatment, which received the Biofield Energy Healing Treatment by a renowned Biofield Energy Healer, Mahendra Kumar Trivedi. The cell viability using MTT assay showed that the cell viability of 3T3-L1 and PBMCs cells was more than 70% indicating a safe and nontoxic profile. The experimental data in PBMCs cells showed that the Biofield Energy Treated Test formulation showed a significant improved telomerase activity by 39.25%, 20.86%, and 17.95% at concentrations 0.01, 5, and 100 µg/mL, respectively as compared with the untreated test formulation group. These results indicate that the Biofield Energy Healing Treatment would be the significant approach to prevent aging-related disorders such as decline cardiovascular diseases, osteoporosis, dementia, osteoarthritis, Alzheimer’s, hypertension, cancer, Parkinson's Disease, Chronic Obstructive Pulmonary Disease (COPD), Stress, Asthma, cataract, age-related macular degeneration (AMD), hearing loss and metabolic disorders.
Keywords: Biofield Energy Healing; SIRT1; PBMCs; Telomerase assay; Aging